PENGARUH RASIO KEUANGAN DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN NON-KEUANGAN DI INDONESIA - Santoso, Michael Adrian; Tjhai, Fung Jin (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The purpose of this research is to obtain empirical evidence about the effect of return on equity, debt to equity ratio, current ratio, firm size, dividend payout ratio, managerial ownership, institutional ownership, and free cash flow on firm value. This research uses samples from all companies except financial sector listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022 with 65 listed non-financial companies used as samples in this research. This sample selection used the purposive sampling method with research data with a total of 195 data and analysis using multiple linear regression. The results of this research showed that return on equity and debt to equity ratio have positive effect on firm value. Higher return on equity shows that the company is generating higher profits and the profits can exceed the cost of equity, thereby giving a positive impression to shareholders which can increase firm value. Higher debt to equity ratio means that the company is more confident about the company’s prospects and increases the management discipline in managing company’s financial, which makes investors interested in buying shares, thereby increasing firm value. Other independent variables such as current ratio, firm size, dividend payout ratio, managerial ownership, and institutional ownership have no effect on firm value.